2012
DOI: 10.1155/2012/585726
|View full text |Cite
|
Sign up to set email alerts
|

Williams-Beuren's Syndrome: A Case Report

Abstract: Williams-Beuren syndrome is a rare familial multisystem disorder occurring in 1 per 20,000 live births. It is characterized by congenital heart defects (CHD), skeletal and renal anomalies, cognitive disorder, social personality disorder and dysmorphic facies. We present a case of Williams syndrome that presented to us with heart murmur and cognitive problem. A 5-year-old girl referred to pediatric cardiologist because of heart murmurs. She had a systolic murmur (2-3/6) in right upper sternal border with radiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Williams Syndrome (WS) is a well-recognized, multi-system genetic disorder characterized by facial anomalies described as elfin faces, cognitive dysfunction, growth abnormalities, congenital heart defects, and other very rare manifestations [ 1 ]. Most (90%) of the cases of WS occur due to deletion at chromosome 7q11.23, which also includes the elastin gene [ 2 ]. The frequency of WS has been estimated to be 1 in 20,000 births, with most of the patients with a normal life expectancy [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Williams Syndrome (WS) is a well-recognized, multi-system genetic disorder characterized by facial anomalies described as elfin faces, cognitive dysfunction, growth abnormalities, congenital heart defects, and other very rare manifestations [ 1 ]. Most (90%) of the cases of WS occur due to deletion at chromosome 7q11.23, which also includes the elastin gene [ 2 ]. The frequency of WS has been estimated to be 1 in 20,000 births, with most of the patients with a normal life expectancy [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of WS has been estimated to be 1 in 20,000 births, with most of the patients with a normal life expectancy [ 3 ]. Diagnosis of Williams Syndrome is mainly clinical, but detecting genetic abnormality by fluorescence in situ hybridization (FISH) aids in the diagnosis [ 2 ]. Existing literature has delineated the common clinical manifestations of this uncommon disorder [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that the IQ of these patients’ range between 40 and 90 [ 5 ]. The vast majority of WS cases diagnosed on clinical basis have demonstrated deletion of chromosomes 7q11.23 that has been detected by FISH (fluorescent in situ hybridization) [ 6 ]. Gene mapping has been capable of detecting various elastin mutations that have been attributed to cardiovascular manifestations of WS as isolated supravalvular aortic stenosis [ 7 ].…”
Section: Introductionmentioning
confidence: 99%